Dental and Oral Health with Periodontitis: Knowledge in Elderly T2DM in Surabaya - Indonesia - Dyah Harum Kartika; Ratih Larasati; Sunomo Hadi; Bambang Hadi Sugito; Sri Hidayati; Isnanto (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2025)
Type 2 Diabetes Mellitus (T2DM) is a chronic condition that affects various aspects of health, including dental and oral health. Diabetes and periodontitis are the most prevalent human diseases. Diabetes worsens the periodontal condition, but periodontitis also hampers glycemic control in diabetic patients. The study aimed to analyze the relationship between knowledge of oral health maintenance and the incidence of periodontitis among elderly patients with Type 2 Diabetes Mellitus (T2DM) at the Tanah Kalikedinding Health Center, Surabaya. The cross-sectional study involved 46 elderly participants diagnosed with T2DM. Data were collected using a dental and oral health maintenance knowledge questionnaire and the Community Periodontal Index of Treatment Needs (CPITN). The majority of respondents were women (73.9%) aged 60-70 years (91.3%), with most having only a junior high school education (47.8%). Knowledge levels were generally low, with 54.35% of respondents classified as having poor knowledge. Most respondents (80.4%) had severe periodontitis, as indicated by CPITN scores. The Pearson correlation test revealed no significant relationship between knowledge levels and CPITN scores (r = -0.134, p = 0.374), suggesting that knowledge about dental and oral health maintenance does not significantly influence the incidence of periodontitis in this sample. The findings highlight the need for comprehensive interventions to improve dental and oral health among elderly T2DM patients, focusing not only on increasing knowledge but also improving access to dental care and promoting healthy lifestyle practices. These efforts are essential to reducing the prevalence of severe periodontitis in this vulnerable population.